ECONOMIC POLICIES ON RICE COMMODITY AND WELFARE - Asaad, Muhammad (Economic Journal of Emerging Markets, 2012)
This study aims at determining the impacts of economic policies on rice and welfare in Indonesia. It estimates a simultaneous equation model with two-stage least squares method, using secondary data from 1979 until 2008. The simulation of partial policy will be a trade-off for the producers and consumers of rice. The policy of the floor grain price is still needed to respond to the increased production of rice. The paper suggests that if the input subsidy is taken out, it should be preferably followed by the increase in output, and at least, the rising percentage should be in the same number so that the policy will be better off. Keywords: Welfare, trade-off, better-off, simultaneous equation model JEL classification numbers: Q13, Q18